1988
DOI: 10.1007/bf02512599
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory study on the predatory mite, Typhlodromus pyri (Acarina: Phytoseiidae). II The effect of temperature and prey consumption on the numerical reponse of adult females

Abstract: SummaryThe numerical response of adult female T. pyri feeding on different levels of ERM larvae, and at a range of temperatures was examined. The duration of the pre‐oviposition period decreased as larval consumption increased, and the rate of oviposition was linearly related to the rate of consumption of larvae. Mathematical models were used to describe these relationships in terms of temperature and consumption of ERM larvae. The results were discussed in relation to the nature of the T. pyri/ERM interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The results of this study agree well with those reported by Badii and McMurtry (1988), Santos (1975) and Hayes (1988) using leaf discs.…”
Section: Discussionsupporting
confidence: 83%
“…The results of this study agree well with those reported by Badii and McMurtry (1988), Santos (1975) and Hayes (1988) using leaf discs.…”
Section: Discussionsupporting
confidence: 83%
“…Sabelis (1985) reported that temperature has a substantial effect on the rate of oviposition through changes in the duration of oviposition period. According to Hays (1988), a substantial decrease in fecundity from 29.3 to 6.2 eggs/female was observed with increasing temperature from 25 to 26.5°C. The cause of higher differences in fecundities remains unexplained, but it might be due to the fact that the studies were conducted under different climatic conditions, different strains of the predator were used and different amounts and varieties of food were available to the predatory mites.…”
Section: Discussionmentioning
confidence: 96%
“…The reason was that the females which fed on C. ribis had a relatively shorter oviposition period and longer preoviposition period. The prolongation of preoviposition period and reduction of total fecundity were also noted by Herbert (i 956, 1961) and Hayes (1988) in T. pyri females with a small supply of prey. However, in assessing individual females of both groups a negative correlation between total fecundity and duration of preoviposition period was not found.…”
Section: Parameters Of Reproductionmentioning
confidence: 85%
“…Temperature has a substantial effect on the rate of oviposition through changes in the duration of oviposition period, whilst total fecundity remains constant within a wide range of temperatures (Sabelis, 1985). According to Hayes (1988), optimal temperature for fecundity in T. pyri is between 20 and 25°C, at which mean fecundity was up to 29.3 eggs. He found a substantial decrease in fecundity at 26.5°C (6.2 eggs per female).…”
Section: Parameters Of Reproductionmentioning
confidence: 99%